Hierarchies of evolutionary radiation in the world's most species rich vertebrate group, the Neotropical Pristimantis leaf litter frogs. Issue 8 (17th November 2018) - Waddell, Emily H.; Crotti, Marco; Lougheed, Stephen C.; Cannatella, David C.; Elmer, Kathryn R.
Abstract : The Neotropical leaf litter frog genus Pristimantis is very species-rich, with 526 species described to date, but the full extent of its diversity is much higher and remains unknown. This study explores the phylogenetic processes and resulting evolutionary patterns of diversification in Pristimantis . Given the well-recognised failure of morphology- and community-based species groups to describe diversity within the genus, we apply a new test for the presence and phylogenetic distribution of higher evolutionary units. We developed a phylogeny based on 260 individuals encompassing 149 Pristimantis presumed species, sampled at mitochondrial and nuclear genes (3718 base pair alignment), combining new and available sequence data. Our phylogeny broadly agrees with previous studies, both in topology and age estimates, with the origin of Pristimantis at 28.97 (95% HDP =21.59 – 37.33) million years ago (MYA). New taxa that we add to the genus, which had not previously been included in Pristimantis phylogenies, suggest considerable diversity remains to be described. We assessed patterns of lineage origin and recovered 14 most likely (95% CI: 13–19) phylogenetic clusters or higher evolutionary significant units (hESUs) within Pristimantis . Diversification rates decrease towards the present following a density-dependent pattern for Pristimantis overall and for most hESU clusters, reflecting historical evolutionary radiation. The timing of diversification suggests that geological events in the Miocene, such as Andes orogenesis and Pebas system formation and drainage, may have had a direct or indirect impact on the evolution of Pristimantis and thus contributed to the origins of evolutionary independent phylogenetic clusters.